Pengaruh Pelatihan Model POT EMAS terhadap Kemampuan Keluarga Merawat Lansia dengan Diabetes Melitus - Tien Hartini; Yeti Resnayati; Agus Sri Sukoco; Supriadi; Raden Siti Maryam (Jurnal Vokasi Keperawatan (JVK), 2023)
In general, many elderly people complain of various kinds of symptoms that are felt due to a decrease in body condition. Apart from being affected by the decline in the elderly, it is also influenced by a lack of knowledge, attitudes, and family behavior in caring for the elderly. This study aims to obtain an overview of the effect of the Energetic, Helpful, Active and Patient Parent Assistance Model, abbreviated as "POT GOLD", on increasing the ability of families to care for the elderly with Diabetes Mellitus. Quasi-experimental research was used with a pretest-posttest design without a control approach. Respondents were elderly people with families in the work area of the Pulo Gebang Village Health Center, Cakung District, totaling 30 respondents obtained by purposive sampling technique. Data analysis used a paired t-test and showed that there was a significant difference between before and after the POT EMAS model training (pvalue 0.001). This shows that training on the POT EMAS model has a significant effect on increasing knowledge, attitudes and behavior of families in caring for the elderly with Diabetes Mellitus, as well as being able to monitor the stability of blood sugar levels in the elderly. Thus the results of this study can be used as a form of elderly health services in the family to carry out various interventions related to family and community empowerment. Qualitative research on family experiences with this model can be carried out.